NVC: Non verbal communication, studies and applications - Hickson III, Mark; Stacks, Don W. (Subuque: Wm. C. brown publishers, 1985)
Contents: section 1: introduction. section 2: subcodes and studies. section 3: applications.
Glossary p. 307 - 312 index p. 313 - 318.
Keywords: Comunicación no Verbal